2017
DOI: 10.1136/vr.103997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating veterinary practitioner perceptions of communication skills and training

Abstract: Response rates and demographics 8A total of 1,190/3000 responses were received from the UK (39.7% 9 response rate), and 584/3000 responses were received from the US 10 (19.5% response rate). The overall response rate was 29.6% 11(1,774/6000). Mix of respondents was 57.3% female (1,013/1,768) and 12 42.7% male (755/1,768), with similar gender mix in the UK and US. 13Range in age was 23 years to 79 years (median age 41 years), with a 14 higher median age in the US (47 years) than in the UK (37 years). 15 Themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition to these a priori codes, initial codes were also identified using inductive analysis. 12 Collaborative coding was carried out by a second researcher (KC) to check the accuracy and consistency of the coding structure. Following an iterative analytical process, a mind map was built to illustrate the key themes and subthemes identified during the interview process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these a priori codes, initial codes were also identified using inductive analysis. 12 Collaborative coding was carried out by a second researcher (KC) to check the accuracy and consistency of the coding structure. Following an iterative analytical process, a mind map was built to illustrate the key themes and subthemes identified during the interview process.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have suggested changes in communication skills training, some limitations still remain in group training. For example, group training might compromise individual needs [55]. Hence, the idea of tailor-made training has been introduced, but it was not concluded to be a practical strategy in large group training [55].…”
Section: Training On Veterinary Communication Skillsmentioning
confidence: 99%
“…For example, group training might compromise individual needs [55]. Hence, the idea of tailor-made training has been introduced, but it was not concluded to be a practical strategy in large group training [55]. One study suggested that when graduated students start practicing veterinary medicine, providing more continuous professional training (CPT) can reduce the communication skill gaps between senior veterinarians who graduated before 2000 and current veterinarians [13].…”
Section: Training On Veterinary Communication Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Veterinary communication skills and training have been given increased emphasis in recent years, following a similar development in human medicine. [5][6][7][8][9] One of the suggested hallmarks of efective communication skills is client-or relationship-centred communication. 10 This is characterised, among other ways, as a communication style that emphasises two-way communication between the veterinary surgeon (and/or staf members) and the client, including recognising the client's interests, emotions, and concerns.…”
Section: Communicating With Clients About Safety Measures In the Vetementioning
confidence: 99%